Studi Literatur : Perancangan Dan Implementasi Sistem Peminjaman Dan Pengembalian Barang Digital Berbasis Web Pada Perpustakaan Digital - Saipullah, Fasya; Simatupang, Reza Riansyah; Batubara, Ihsan Abdul Hafiz; Wijaya, Abdul Rahman; Gunawan, Indra (Journal of Computer Science and Information System(JCoInS), 2025)
This study aims to determine how to design and implement a web-based digital goods lending and returning system in a digital library. This study uses a qualitative descriptive approach with a literature study method. The results of the study indicate that the implementation of a web-based digital goods lending and returning system generally makes a major contribution to increasing efficiency, effectiveness, and security in the administrative process, both in educational environments, companies, and other sectors. The manual system that has been used so far has been proven to have many limitations, such as data inaccuracy, slow information search processes, and potential recording errors that can affect the reliability of stock and service data. By utilizing web-based technology, the lending and returning system can be designed to be more interactive, responsive, and integrated, making it easier for users to access and manage data in real-time. In addition, the use of this technology can also minimize human error, speed up workflows, and improve overall service quality.